The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11011-017-0010-8
|View full text |Cite
|
Sign up to set email alerts
|

13 novel putative mutations in ATP7A found in a cohort of 25 Italian families

Abstract: ATP7A is a copper-transporting P-type adenosine triphosphatase whose loss of function leads to the Menkes disease, an X-linked copper metabolism multi-organ disorder (1 in 100.000 births). Here we document our experience with the ATP7A linked diseases in Italy. We analyzed the exonic structure of the ATP7A gene in 25 unrelated Italian families and studied the variants of unknown significance. We identified 22 different DNA alterations, 13 of which first reported in this study. The classical Menkes phenotype wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The compendium of curated variants encompasses a total of 602 variant entries in the ATP7A gene. These variants were derived from a total of 64 publications [6] , [8] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] and encompassed variants reported from 17 countries. Of the total compendium of variants, a total of 404 variants were unique and a large majority of variants mapped to exons 18,18% (328/404), while a small number were intronic 12% (49/404), splicing 6.18% (25/404) and UTR 0...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compendium of curated variants encompasses a total of 602 variant entries in the ATP7A gene. These variants were derived from a total of 64 publications [6] , [8] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] and encompassed variants reported from 17 countries. Of the total compendium of variants, a total of 404 variants were unique and a large majority of variants mapped to exons 18,18% (328/404), while a small number were intronic 12% (49/404), splicing 6.18% (25/404) and UTR 0...…”
Section: Resultsmentioning
confidence: 99%
“…OHS. It is observed that MD with milder form are characterized by mutations showing some residual activity while mutations with no residual activity manifested classical form of MD [41] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the Wilson disease, where mutation is located on autosome, the Menkes disease is related to X chromosome so the disease is manifested in men with mutation in their chromosome or in a woman in X-linked recessive inheritance mode. In the Menkes disease, gene ATP7A for copper-transporting P-type ATPase is mutated (60,61). Various mutations can occur in the ATP7A gene resulting in the lack of the coded P-type ATPase in the Trans-Golgi Network, which is natural site, where it is active and the lack of the copper concentration in the Golgi apparatus follows (62).…”
Section: Wilson and Menkes Disease As Genetically Determined Disordermentioning
confidence: 99%
“…The overall incidence is 1 in 100,000–250,000 births, grouping MD as an ultra-rare orphan disease [ 3 ]. Genetically, loss-of-function alterations in ATP7A , resulting from point mutations, short indel, large deletions, and duplications, account for all the cases reported to date [ 1 , 2 , 4 , 5 , 6 , 7 ]. The ATP7A protein facilitates the export of copper from non-hepatic tissues and delivers copper to the secretory pathway for incorporation into copper-dependent enzymes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%